Acceptability of a novel trampoline intervention in rehabilitation for Parkinson’s disease. Perceived barriers and facilitators - Domingos, Josefa (2022)
Communication: Abstract book of the 5th World Parkinson Congress, Kyoto, Japan, June 4–7, 2019.